New towns as growth centres A Case Study in Nigeria - E. Sokari George (Indonesian Journal of Geography, 1986)
This paper criticizes the selection of seven new towns as growth centres in Rivers State. However, based upon financial constraint and other variables, it suggested only two locations suitable for growth centres. These centres are integrated with rural development policies to function as alternative destinations for rural migrants to the state's capital city and to strengthen the service hierarchies in the rural region, The general arguments are illustrated with a case study of Rivers State of Nigeria.